Rationalized Rules: A Critical Metaphor Analysis of Selected Autobiographical Political Discourse - Muhammad Akbar Khan, Abdullah Jan Abid (JSSH, 2023)
This paper aims at giving a critical analysis of the metaphors employed by Benazir Bhutto and General Musharraf in their political autobiographies, viz., Daughter of the East and In the Line of Fire, respectively. The issues of identity, power and their rationalization and ideology are the main concern and focus in the selected political discourses.